Multi-Omics Landscape of DNA Methylation Regulates Browning in “Fuji” Apple - Wang, Lihua; Tang, Tiantian; Wang, Wenjun; Zhang, Jie; Wang, Zhidong; Wang, Fengzhong (Frontiers in Nutrition, 2022)
Browning seriously affects quality of fresh-cut fruits, and its mechanism was thought to be PPO in the past. A way of non-different PPO browning was found in our previous studies. However, the landscape of this browning way is still unclear in “Fuji” apples. Multi-omics (methylomics, transcriptomics and proteomics) methods were performed to the global profiles of DNA methylation, genes and proteins expression. We employed two natural bud mutation varieties of apple as materials, and found a positive correlation between browning index (BI) and methylation (5mC%, MdCMT3 and MdCMT3c) and a negative correlation between BI and demethylation (MdROS1 and MdDME). DNA methylation inhibitor 5-azacytidine can delay apple browning. Further analysis showed that methylated-NCA1 and OMT1 increased significantly in apple browning. Methylated-NCA1 might inhibits to NCA1 gene expression and resulted in the decline of CAT activity, thereafter increased significantly apple browning. This findings insight into a new pathway and landscape that DNA hyper-methylation significantly accelerated the browning in “Fuji” apple.